Egypt Human Development Report 2000/2001.
The Report analyzes from a human development perspective the opportunities and constraints that today face Egypt’s sizeable youth population, where 25 percent of Egyptians are between the ages of 18 and 29. It examines the role of youth in Egypt’s development process looking at issues including education, health, gender, poverty, employment, housing, and participation in society. The Report also showcases success stories of youth-centred initiatives, programmes, and projects, calling for greater consultation and communication between young people, the Government and civil society. In conclusion, the Report highlights nine main messages to ensure youth’s inclusion and full participation in society.